2021
DOI: 10.3390/ijerph18062976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School-Based Physical Activity Programs on Health-Related Physical Fitness of Korean Adolescents: A Preliminary Study

Abstract: As adolescents spend the majority of their time focused on exams and assignments, they do not have sufficient time to engage in physical activity; this lack of physical activity is an important public health concern. This study aimed to investigate how school-based physical activity programs affect the health-related physical fitness of adolescents in the Republic of Korea. For this study, a total of 120 high school students participated in a school-based physical activity program that included badminton and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
1
20
1
1
Order By: Relevance
“…Nevertheless, participants in the present study performed worse than Korean table tennis players aged between 20 and 25 years [41]. The results observed in the SAR test were lower than previously observed in table tennis players, in corresponding age groups [8,40,43]. Differences in the results in the physical tests between studies might be due, in part, to the comparison of performance between different categories.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Nevertheless, participants in the present study performed worse than Korean table tennis players aged between 20 and 25 years [41]. The results observed in the SAR test were lower than previously observed in table tennis players, in corresponding age groups [8,40,43]. Differences in the results in the physical tests between studies might be due, in part, to the comparison of performance between different categories.…”
Section: Discussioncontrasting
confidence: 81%
“…Pradas de la Fuente et al [37] observed a lower performance (i.e., 23%) in a previous study in the U12 category, but Pullinger et al [44] and Taş [43] observed similar results in the U12 and U14 categories of table tennis players. As regards the HCMJAS, the table tennis players in the present study performed better than Korean table tennis players [40], had similar results comparing with U12 table tennis players [43] and U14 table tennis and tennis players [20,44], but worse than junior tennis players from the USA, in corresponding age groups [14]. The S5M and S10M results were similar to those observed in U14 table tennis [44] and tennis players, in corresponding age groups [20].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Considering this gap in the existing research, this study attempted to analyze changes in health-related physical fitness before and after the COVID-19 pandemic for elementary and middle school students in Korea using data obtained through the physical fitness promotion system (PAPS). Since 2010, all public and private schools in Korea have participated in the PAPS, which aims to evaluate physical fitness and provide exercise-related guidance to elementary, middle, and high school students based on assessments of physical factors such as power, flexibility, cardiorespiratory endurance, muscle endurance, and body composition [ 24 , 25 ]. The impact of PAPS has been assessed by various studies.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the benefits of badminton in terms of improving physical fitness, five studies reported benefits in adolescents of both sexes, such as improved muscular strength and endurance, explosive strength, power, flexibility, and cardiorespiratory fitness [ 26 , 34 , 35 , 73 ], obtaining significant improvements in all of the aforementioned parameters, with the only exception being body composition [ 35 ].…”
Section: Discussionmentioning
confidence: 99%